Immunocytological diagnosis of primary cerebral non-Hodgkin's lymphoma. - Lai, A P (1991)
Four men with primary cerebral non-Hodgkin's lymphoma diagnosed by immunocytological analysis of cerebrospinal fluid (CSF) presented with cranial nerve palsies. All had CSF lymphocytoses and low CSF glucose. The cell phenotypes were two T cell tumours, one B cell, and one null. A review of 13 previously recorded cases of immunocytologically diagnosed CNS non-Hodgkin's lymphoma showed that there were 10 B cell, two T cell, and one null tumour. Overall (17 cases) the cell phenotype distribution was 65% B cell, 24% T cell, and 11% null. High CSF lymphocyte counts were found in 94%, proteinosis in 85%, and low CSF glucose in 87%. In contrast to the B cell tumours, all of the T cell tumours were diagnosed by CSF cytology before being visualised radiologically. It is suggested that all CSF lymphocytes (greater than 5 x 10(6)/ml) should be immunohistochemically typed to permit earlier diagnosis of CNS non-Hodgkin's lymphoma.